(2x + 5)^2 = (x - 1)^2
Key note: Whenever you take the square root of both sides of an equation, you have to add a "plus or minus" on the right hand side. This is what the "square root" method is; the addition of the "+/-", and the three people above me failed to recognize that (until some recent editing). That is,
2x + 5 = +/- (x - 1)
This leads to two equations:
2x + 5 = x - 1
2x + 5 = -(x - 1)
2x + 5 = x - 1 means
x = -6
and 2x + 5 = -(x - 1) means
2x + 5 = -x + 1, so
3x = -4, x = -4/3
So x = {-6, -4/3}
Let's verify:
If x = -4/3, then
LHS = (2(-4/3) + 5)^2
LHS = (-8/3 + 5)^2
LHS = (-8/3 + 15/3)^2
LHS = (7/3)^2 = 49/9
RHS = (-4/3 - 1)^2
RHS = (-4/3 - 3/3)^2
RHS = (-7/3)^2 = 49/9
LHS = RHS, so x = -7/3 is a definite answer.
Test x = -6. Then
LHS = (2(-6) + 5)^2 = (-12 + 5)^2 = (-7)^2 = 49
RHS = (-6 - 1)^2 = (-7)^2 = 49
LHS = RHS, so x = -6 is another definite answer.
2007-01-16 22:08:59
·
answer #1
·
answered by Puggy 7
·
2⤊
1⤋
First: eliminate the exponents > find the square root of both sides
V`(2x + 5)^2 = V`(x - 1)^2
V`(2x+5)(2x+5) = V`(x - 1)(x - 1)
*Since you have two of the same expressions (the expression are repeated twice), pull out one of the expressions on both sides....
2x + 5 = x - 1
Sec: subtract 5 from both sides...
2x + 5 - 5 = x - 1 - 5
2x = x - 6
*Subtract "x" from both sides...
2x - x = x - x - 6
x = - 6
2007-01-17 11:05:29
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
1⤋
(2x+5)^2 = x^2-2x+1
2x+5 = square root of x^2-2x+1
2x+5 = x - square root of 2x +1
2x-x+square root of 2x = 1-5
x+square root of2x = -4
x+1.414x = -4
2.1414x = -4
x = -4/2.1414
= -1.87
2007-01-17 06:37:39
·
answer #3
·
answered by loally 2
·
0⤊
2⤋
(2x + 5)² = (x - 1)²
2X + 5 = square root of (x – 1)2
2X + 5 = x – 1
2x – x = -1 – 5
X = -6
2007-01-17 06:07:59
·
answer #4
·
answered by mx_kn_an 2
·
1⤊
2⤋
Its just by square-rooting them
2x+5=x-1
=>2x-x=-1-5
=>x=-6
k
2007-01-17 06:14:55
·
answer #5
·
answered by alpha 7
·
1⤊
2⤋
hey this is the perfect soln:
(2x + 5)² = (x - 1)² a²-b²=(a+b)(a-b)
= (2x + 5)² - (x - 1)²=0
= (2x+5+x-1)(2x+5-x+1)=0
= (3x+4)(x+6)=0
hence ur X is -4/3 or x=-6
njoy..
2007-01-17 06:11:47
·
answer #6
·
answered by keep life simple 1
·
2⤊
1⤋
Soooooooo Easyyyyyyyyyy !!!
(2x + 5)^2 = (x -1)^2
4x^2 + 20x + 25 = x^2 - 2x + 1
3x^2 + 22x +24 = 0
x1 = -4/3
x2 = -6
2007-01-17 06:11:58
·
answer #7
·
answered by crystal_heart100 5
·
1⤊
2⤋
follow this:
(2x+5)^2-(x-1)^2=0 => ((2x+5)+(x-1))*((2x+5)-(x-1))=
(3x-4)*(x+6)=0
=>x=4/3 or -6
2007-01-17 07:04:07
·
answer #8
·
answered by 1145 2
·
2⤊
0⤋
taking sqrt
2x+5=-+-(x-1) So you have two cases
2x+5=x-1===> x=-6
2x+5= -x+1 ===> 3x=-4 and x=-4/3
both values solve the problem
2007-01-17 06:49:47
·
answer #9
·
answered by santmann2002 7
·
2⤊
0⤋
sqrt of [((2x + 5)^2)=((x - 1)^2)]
2x + 5 = x - 1
2x - x = -1 - 5
x = -6
2007-01-17 07:06:14
·
answer #10
·
answered by iamdeyb 2
·
1⤊
1⤋